2016
DOI: 10.21451/1984-3143-ar797
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between follicle and corpus luteum diameter, blood flow, and progesterone production in beef cows and heifers: preliminary results

Abstract: The aim of the present study in beef cattle was to investigate potential differences in follicle size and follicle wall-blood flow between cows and heifers and to compare follicle wall-blood flow between smaller and larger follicles. Cows and heifers were treated with a synchronization protocol and follicles and CLs were measured and evaluated for blood flow. Pregnancy diagnosis was performed on day 50 of the protocol. Cows had larger (P < 0.008) follicles than heifers. Cows, heifers, and pregnant and non-preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
(76 reference statements)
9
14
0
Order By: Relevance
“…Thus, although daily ovary scanning was not performed, there is a possibility that hCG acted on dominant follicles during the first follicular wave (Day 6 after ovulation) evoking accessory ovulation. No differences in CL diameter, blood flow, and P4 concentration were reported between pregnant and nonpregnant cows until Day 6 following ovulation in a previous study (Tarso et al, 2016). In the present study, similar conditions were noted in Santa Inês sheep.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, although daily ovary scanning was not performed, there is a possibility that hCG acted on dominant follicles during the first follicular wave (Day 6 after ovulation) evoking accessory ovulation. No differences in CL diameter, blood flow, and P4 concentration were reported between pregnant and nonpregnant cows until Day 6 following ovulation in a previous study (Tarso et al, 2016). In the present study, similar conditions were noted in Santa Inês sheep.…”
Section: Discussionsupporting
confidence: 84%
“…Progesterone concentration depends on the size of the ovulatory follicle and luteal phase. Reducing the size of the ovulatory follicle causes a reduction in the size of the CL and the circulating progesterone concentration in lactating dairy cows [11], [13]. This result is consistent with an early reported that claims that the use of Ovsynch protocol before the initiation of a breeding ovsynch with the time AI can induce ovulation in anovular cows and thus increase the percentage of cows with medium circulating Progesterone [38].…”
Section: The Progesterone Concentration Of Local Pesisir Cattle Insupporting
confidence: 90%
“…The cows involved in this study responded well to the administration of hormone PGF2α. This result shows [13] that the first GnRH, when administered at random stage of the estrus cycle, would induce ovulation in cows with the functional dominant follicle. A new follicular wave would be initiated with the dominant follicle selected during the next 7 days.…”
Section: A Diameter Of the Follicle Of Local Pesisir Cowsmentioning
confidence: 69%
See 1 more Smart Citation
“…The positive correlation between the follicle diameter on day 0 and the CL diameter on day 8 that we detected was also observed in cows (40,41), ewes (42), and mares (43)(44)(45) and could be because the size of the pre-ovulatory follicle would regulate the size of the CL in its early stages, mainly due to a spatial constraint (46). Nevertheless, the vertical diameter of the CL on day 8 was similar between pregnant females (Group I+) and non-pregnant females (Groups I-and II).…”
Section: Figure 4 |supporting
confidence: 86%